Exploring the potential of cold plasma therapy in treating bacterial infections in veterinary medicine: opportunities and challenges - Mohseni, Parvin; Ghorbani, Abozar; Fariborzi, Niloofar (Frontiers in Veterinary Science, 2023)
Cold plasma therapy is a novel approach that has shown significant promise in treating bacterial infections in veterinary medicine. Cold plasma possesses the potential to eliminate various bacteria, including those that are resistant to antibiotics, which renders it a desirable substitute for traditional antibiotics. Furthermore, it can enhance the immune system and facilitate the process of wound healing. However, there are some challenges associated with the use of cold plasma in veterinary medicine, such as achieving consistent and uniform exposure to the affected area, determining optimal treatment conditions, and evaluating the long-term impact on animal health. This paper explores the potential of cold plasma therapy in veterinary medicine for managing bacterial diseases, including respiratory infections, skin infections, and wound infections such as Clostridium botulinum, C. perfringens, Bacillus cereus, and B. subtilis. It also shows the opportunities and challenges associated with its use. In conclusion, the paper highlights the promising potential of utilizing cold plasma in veterinary medicine. However, to gain a comprehensive understanding of its benefits and limitations, further research is required. Future studies should concentrate on refining treatment protocols and assessing the long-term effects of cold plasma therapy on bacterial infections and the overall health of animals.